2006
DOI: 10.1021/jp056330t
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of the Aqueous Liquid−Vapor Interface:  A Comprehensive Particle-Based Simulation Study

Abstract: This research addresses a comprehensive particle-based simulation study of the structural, dynamic, and electronic properties of the liquid-vapor interface of water utilizing both ab initio (based on density functional theory) and empirical (fixed charge and polarizable) models. Numerous properties such as interfacial width, hydrogen bond populations, dipole moments, and correlation times will be characterized with identical schemes to draw useful conclusions on the strengths and weakness of the proposed model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
193
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(228 citation statements)
references
References 72 publications
(193 reference statements)
30
193
2
1
Order By: Relevance
“…The PDM-H2O is a simple isotropic model which is able to reproduce with a small error the electrostatic properties of chloride-water dimers. 24 Nevertheless, as for other models used in the previous studies, 30,31 when it is transferred to condensed phase, it does not perform so well since the water dipole moment is underestimated by ϳ25%. On the other hand, the PD2-H2O model performs fairly well, showing a small shift of ϳ0.2 D with respect to the ab initio curve.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…The PDM-H2O is a simple isotropic model which is able to reproduce with a small error the electrostatic properties of chloride-water dimers. 24 Nevertheless, as for other models used in the previous studies, 30,31 when it is transferred to condensed phase, it does not perform so well since the water dipole moment is underestimated by ϳ25%. On the other hand, the PD2-H2O model performs fairly well, showing a small shift of ϳ0.2 D with respect to the ab initio curve.…”
mentioning
confidence: 77%
“…For example, given that the surface propensity of the chloride ion ͑and of the bigger halogenide anions͒ is explained as a minimum in the free energy at the surface due to ion polarization, 3 an exact modeling of polarizable interactions would provide more accurate quantitative estimates of the phenomenon. In the Introduction, it was pointed out that the solvent polarization also plays an important role; nevertheless, in some recent studies, 30,31 it was found that water molecules are underpolarized as compared to Car-Parrinello simulations. This is clearly shown in Fig.…”
mentioning
confidence: 99%
“…Molecular dynamics simulations provide quantitative predictions of ion concentrations at the surface and of the distributions of ions with depth, although the results depend on the interaction potentials used (11,34). Surface spectroscopy measurements provide important experimental validation of inorganic ion partitioning but have not yielded surface concentrations because it is not feasible to determine the depth being probed (6,8,9,14).…”
Section: Discussionmentioning
confidence: 99%
“…61 For example, Kuo et al 62 used tan-hyperbolic function to fit the density profiles for various water models. On the other hand, Sides et al 63 and Ismail et al 64 used both tan-hyperbolic and error function for the Lennard-Jones fluid and various water models, respectively, and obtained the interfacial width.…”
Section: B Vapor-liquid Interfacial Tension Under Confinementmentioning
confidence: 99%